IDENTIFIKASI KADAR VITAMIN C PADA DAGING DAN KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Syarifuddin, Aminah Nur; Zantrie, Rezky; Teresia Marbun, Romauli Anna (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Introduction: Vitamin C is one of the nutrition acted as a antioxidants and effective addres free radicals can be destructive cells or tissue. Fruits are a source of vitamins C, which is a dragon red. Part of the dragon red during this rarely used is the skin. The dragon fruit is very useful to health, but in fact only thought of as waste farming has yet to be used as a good. This study aims to determine comparison levels of vitamin C on the flesh and the dragon red (Hylocereus polyrhizus) with a method spectrophotometry UV-Visible. Method: This type of research using the method of true experimental reseach stage includes preparation of samples, qualitative test,quantitative test, making the solution of the parent raw materials, determination of wavelength of vitamin C and manufacture of the calibration curve. The sample of this study is the flesh and the dragon red (Hylocereus polyrhizus). Results: Based on the results revealed that the fles and the dragon red (Hylocereus polyrhizus) contain vitamin C. Discussion: Levels of vitamin C on the flesh the dragon red of 0.05888 mg/mL and The levels of vitamin C on the skin the dragon red of 0.02533 mg/mL .